FASTING AND POSTPRANDIAL HYPOGLYCEMIA IN AN ADOLESCENT PRESENTING WITH ENDOGENOUS HYPERINSULINEMIC HYPOGLYCEMIA LIKELY INSULINOMA: A CASE REPORT - Khan, Nashriq Khan Adam; Abdullah, Noor Rafhati Adyani (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Hypoglycaemia is an uncommon clinical problem in individuals without diabetes mellitus. It is a clinical syndrome with various causes in which low plasma glucose leads to hypoglycaemic symptoms and signs that resolve when the plasma glucose is raised. The diagnosis of a true hypoglycaemic disorder requires fulfilment of these specific criteria (Whipple’s triad). Once the presence of a hypoglycaemic disorder is verified, a detailed clinical history often suggests a specific underlying cause. Insulinoma is a type of functional neuroendocrine tumour characterized by hypersecretion of insulin, causing hypoglycaemia, characteristically fasting hypoglycaemia. We describe a patient with insulinoma with both fasting and postprandial hypoglycaemia. CASE A pre-morbidly healthy 12-year-old male presented with recurrent hypoglycaemia for 3 months. He experienced a severe episode of hypoglycaemia manifesting as seizure with blood glucose of 1.4 mmol/L. Symptoms resolved after glucose administration. He developed progressive weight gain over the course of 4 years. His BP was 120/72, PR 98, BMI 30 with absence of acanthosis nigricans. Blood investigation during clinic visit revealed asymptomatic hypoglycaemia mediated by endogenous hyperinsulinemia, with random blood glucose of 1.7 mmol/L (<3 mmol/L), serum insulin 364.8 pmol/L (>20 pmol/L) and C-peptide 1495 pmol/L (>200 pmol/L). Mixed meal test confirmed fasting hypoglycaemia, with RBS of 2.5 mmol/L, insulin 300 pmol/L, C-peptide of 1145pmol/L. At 120 minutes (postprandial) following the test, RBS was 2.3 mmol/L, insulin 557 pmol/L, C-Peptide 2282 pmol/L. Prolonged supervised fasting test revealed hypoglycaemia after 4 hours with RBS 2 mmol/L, insulin 286.8 pmol/L and C-peptide 1459 pmol/L. Beta-Hydroxybutrate remained suppressed at 0.1 mmol/L following fasting. Sulphonylureas screening was negative. HbA1c was 4.2% and serum Ca (corrected) was 2.22 mmol. CT pancreatic protocol revealed a hypervascular lesion (1.9 x 2.0 x 2.9cm) at the pancreatic head. Diazoxide was initiated to prevent hypoglycaemia and it was well tolerated. The patient is planned for surgical resection of the pancreatic lesion which is likely to be an insulinoma. CONCLUSION Recurrent hypoglycaemia requires careful and comprehensive assessment to diagnose a patient. Around 20% of insulinoma patients have both fasting and postprandial hypoglycaemia needing clinical suspicion and prompt assessment to improve outcomes for these patients.